MIGRAÇÃO, TRÁFICO DE PESSOAS E TRABALHO DOMÉSTICO - Natália Ramos (Universidade Federal do Maranhão, 2014)
The human migrations become nowadays more complex, feminized, qualified, internationalized and individualized. The human migration process has been reaching all continents, countries, genders, social classes and generations. They are rooted in the origin of the identity, family, social, industrial, cultural and political changes, involving various fields of public and private spheres. It is possible to witness in recent decades, not only to the growth and diversification of international migration, mostly female, but also, the generalization and globalization of migrant female labor, many women migrants finding work in domestic service. The human migrations, especially the female migration, human trafficking, as well as, the social, labor and gender inequalities are the object of research and concern of the states, national and international organizations and public policies in different sectors. In this context, it is important to develop an integrated and multi/interdisciplinary approach for migration, based mainly, on human rights and appropriate public policies, recognizing migration, especially, the women migration, not only as an essential factor of development, but also, a factor of the vulnerability, discrimination and associated exploration.